1973
DOI: 10.2307/2412306
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Relationships in Pacific Salmon and Related Trout Based on Protein Variations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
2

Year Published

1973
1973
2005
2005

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 20 publications
3
36
1
2
Order By: Relevance
“…The visualization of 'background' bands was subsequently shown to be due to alcohol dehydrogenase (EC 1.1.1.1) (ADH) isozymes reacting with methanol (used to store cellogel sheets prior to use) still present in the gels after soaking in buffer solution. (Avise and Smith 1974a), and 0.01-0.13 ; Utter et al 1973). Some estimates for populations of the cave-dwelling fish Astyanax mexicanus [0.00-0.41 (Avise and Selander 1972)l are considerably higher, however, than those reported above.…”
Section: Protein Variation Between Speciesmentioning
confidence: 98%
“…The visualization of 'background' bands was subsequently shown to be due to alcohol dehydrogenase (EC 1.1.1.1) (ADH) isozymes reacting with methanol (used to store cellogel sheets prior to use) still present in the gels after soaking in buffer solution. (Avise and Smith 1974a), and 0.01-0.13 ; Utter et al 1973). Some estimates for populations of the cave-dwelling fish Astyanax mexicanus [0.00-0.41 (Avise and Selander 1972)l are considerably higher, however, than those reported above.…”
Section: Protein Variation Between Speciesmentioning
confidence: 98%
“…Electrophoretic studies of protein variation have been able to resolve evolutionary relationships at the interspecific level as a high proportion of loci tend to be informative and diagnostic at the species level. Work on salmonid species (Utter et al ., 1973; Ferguson & Fleming, 1983; Johnson, 1984; Osinov & Lebedev, 2000) supports the Atlantic salmon being a species distinct from brown S. trutta Richardson, rainbow S. gairdneri Richardson and cutthroat S. clarkii Richardson trout, the other species originally placed in the genus Salmo . However, the studies showed Atlantic salmon forming a distinct cluster with brown trout (Ferguson & Fleming, 1983; Fig.…”
Section: Systematicsmentioning
confidence: 99%
“…Over the past 20-30 years, the questions of salmonid phylogeny and taxonomy were considered with the use of the methods of genetic analysis, including the analysis of allozyme diversity. However, it should be noted that, with rare exceptions (Utter et al, 1973;Ferguson & Fleming, 1983;Osinov, 1989Osinov, , 1991Oleynik & Polyakova, 1992), most studies on phylogenetic relationships in the Salmonidae based on allozyme data are limited to the species of the same genus (Leary et al, 1983;Loudenslager et al, 1986), using in some cases one species of the other genus as an outgroup (Crane et al, 1994).…”
Section: Introductionmentioning
confidence: 99%